Merleau-Ponty, Godard, Sobchack and the spatial aesthetics of Rashomon / Gopalan Ravindran - Ravindran, Gopalan (UPENA, 2006)
Maurice Merleau-Ponty's phenomenological theories have been an important source of inspiration for film theorists like Vivian Sobchack and film makers like Jean-Luc Godard. The Cartesian dichotomy between the subject and object became outmoded with the advent of Merleau-Ponty's conception of reversible subjects and objects. No other film maker bears the imprint of the Pontean view of reversible subjects and objects better than Godard. His approach to film philosophy and film making not only acknowledges the Pontean influence but provides a clear methodological basis for film makers to apply the Pontean phenomenology.